Dynamic Behavior and Natural Frequency of a Geodesic Dome: A Comparative Analysis of Physical and Computational Models Utilizing Recycled Plastic - Ramos Coronel , Pablo Esteban (2025)
This study investigates the dynamic behavior and natural frequency of a geodesic dome constructed with recycled polypropylene type 5, emphasizing its feasibility as a sustainable structural solution. A dual approach combining computational modeling and experimental testing was implemented. The computational model incorporated the material's mechanical properties and was validated against a physical prototype subjected to vibration tests. Results revealed a strong correlation between experimental and analytical data, with minimal discrepancies attributed to model idealizations and real construction conditions. The dome's structural performance demonstrated high rigidity and efficient load distribution, confirmed by short vibration periods and balanced dynamic responses. This research highlights the potential of recycled plastic in geodesic structures, aligning with circular economy principles by promoting material reuse and reducing environmental impact. The findings provide valuable insights into innovative and sustainable construction practices, supporting the integration of recycled materials in dynamic structural applications.